Nivolumab-induced autoimmune diabetes mellitus and hypothyroidism in a patient with rectal neuroendocrine tumor. Issue 4 (3rd July 2020) - Haque, Waqas; Ahmed, Shabina R.; Zilbermint, Mihail
ABSTRACT: We present a rare case of autoimmune diabetes mellitus and hypothyroidism in an elderly man initiated on nivolumab two months prior to admission for treatment of a high-grade neuroendocrine rectal tumor. This patient presented to a local community hospital with one-week history of severe nausea, thirst, and bilateral leg edema. Biochemical studies confirmed the diagnosis of diabetic ketoacidosis in the setting of autoimmune diabetes mellitus and primary hypothyroidism, likely due to nivolumab use. This case illustrates an acute complication due to secondary diabetes mellitus in the setting of a novel anticancer agent. There are three key takeaways for physicians managing patients on nivolumab. First, there should be a discussion of the benefits and risks of immunomodulatory therapy. Second, patients should be tested for immunological and other markers before being started on checkpoint inhibitors. Third, oncologists must be aware of the signs and symptoms of life-threatening hyperglycemia and severe hypothyroidism. Additional studies are needed to identify those patients at highest risk for autoimmune complications.